Pelatihan Pengembangan Modul dan Media Ajar Berbasis Interactive Media Untuk Tenaga Pengajar Di Sekolah Perhotelan Neptune, Kediri - Aji, Mahendra Puji Permana; Sulistyani, Sulistyani; Suhartono, Suhartono; Susanti, Yunik; Khoiriyah, Khoiriyah; Riwayatiningsih, Rika (Universitas Nusantara PGRI Kediri, 2018)
Teaching materials or often referred to as learning materials are the most important part in the learning process, the subject matter is the core of learning activities.Teachers in carrying out the learning process required a teaching material because it is used to assist teachers in teaching and learning activities in the classroom. One of the important problems faced by faculty in learning activities is choosing or determining teaching materials or appropriate learning materials in order to help students achieve competence.This dedication to the community is carried out in the NEPTUNE Kediri hospitality school located at Jl.KH. Hasyim Ashari No.49, Bandar Kidul Kediri. By conducting training on the development of teaching materials and teaching media based on interactive media to the teachers in NEPTUNE it is expected that these teachers can become a) competent teachers according to their field of knowledge, b) the teachers are expected to have the ability to develop teaching materials and teaching media appropriately to suit students' needs.Several meetings were held to present more appropriate materials to the teachers. So that the teachers will have the ability to understand what is needed by their students especially after they graduate from the NEPTUNE.